2019
DOI: 10.1093/molbev/msz114
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy of Sexual Ancestors in Phenotypic Variability, Gene Expression, and Homoeolog Regulation of Asexual Hybrids and Polyploids

Abstract: Hybridization and polyploidization are important evolutionary processes whose impacts range from the alteration of gene expression and phenotypic variation to the triggering of asexual reproduction. We investigated fishes of the Cobitis taenia-elongatoides hybrid complex, which allowed us to disentangle the direct effects of both processes, due to the co-occurrence of parental species with their diploid and triploid hybrids. Employing morphological, ecological, and RNAseq approaches, we investigated the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 97 publications
(147 reference statements)
3
28
1
Order By: Relevance
“…(2014) and Bartoš et al. (2019) documented niche segregation between the Cobitis forms, suggesting some role of ecological factors.…”
Section: Introductionmentioning
confidence: 96%
“…(2014) and Bartoš et al. (2019) documented niche segregation between the Cobitis forms, suggesting some role of ecological factors.…”
Section: Introductionmentioning
confidence: 96%
“…Both cis ‐ and trans ‐regulatory networks show unique patterns of expression in hybrid species, especially when comparing diploid to triploid individuals (Bartoš et al. 2019). Thus, adaptation might proceed just by modifying the innate parental regulatory pathways or genes under relaxed selection.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the effects of allele expression on LOH occurrence using recently published transcription profiles of livers and oocytes in sexual (C. elongatoides, C. taenia) and asexual (ET, EET, and ETT) females (Bartoš et al 2019). While Bartoš et al analyzed different individuals, they used the same reference transcriptome and thus we could investigate the transcription profiles of those genes which carried E-T diagnostic SNPs and were either LOH-positive (E-like or T-like LOH bearing), or LOH-negative, according to present exomecapture results.…”
Section: Loh Is Affected By Gene's Transcriptionmentioning
confidence: 99%
“…Realizing their evolutionary significance and huge practical value to mankind (Mason and Batley 2015), research focused on hybridization and polyploidy intensified and revealed some prominent patterns. For instance, hybrid phenotypes may range from intermediate forms to transgressive expression of novel traits (Bell and Travis 2005;Yoo et al 2014; Bartoš et al 2019); however, often, one parental subgenome is more expressed than the other one, known as expression dominance (Yoo et al 2014;Alexander-Webber et al 2016;Cheng et al 2018). Hybrid and polyploid genomes evolve dynamically and often lose orthologous genes from one or the other parental species in processes referred to as loss of heterozygosity (LOH), genome fractionation, or rediploidization in polyploids (Yoo et al 2014;Lien et al 2016;Du et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation